Analisis Pemanfaatan Teknologi Dan Kepribadian Terhadap Minat Entrepreneurship Mahasiswa Keperawatan Stikes Yatsi 2020 - Imanuddin, Bayu; Ratnasari, Febi (Jurnal Nusantara Mandani, 2022)
This study was conducted to determine the use of proprietary technology and personality changes that have arisen in the interests of entrepreneurship / Entrepreneurship among nursing students in the City of Tangerang, where the entrepreneurship process is a process of applying creativity and innovation in exploiting opportunities to achieve more creative and successful business lives. Subjects and methods: The sample used in this study at 3 health high schools, Muhamadiah University Tangerang, Tangerang Poltekkes and Stikes Yatsi, using Purposive Random Sampling that is on the basis of certain criteria, namely students majoring in nursing. By using a table determining the number of Isaac and Michael D samples obtained 236 Respondents. This research method uses the SEM (Structural Equation Model) method, there are 3 variables used, namely Entrepreneurial Interest as an independent variable while the Utilization of Technology and personality as Variable. While the number of indicators in this study amounted to 19. The results of this study found that. Effect of Technology Utilization (X1). Towards Entrepreneurship Interest (Y) has a standardized estimate (regression weight) of 1.673 or 16.7%. Significantly positive effect The effect of latent Personality (X2) on the 2 latent variable Interest in Entrepreneurship (Y) has a standardized estimate (regression weight) of 7.152 or 71.52% significant positive effect Significantly caused by self-confidence that has so high and can see opportunities and use it. Keywords: Personality, Tangerang City, Entrepreneurship Interest, Nursing Student, Technology Utilization